2020
DOI: 10.1021/acs.jmedchem.9b01924
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Morphine-Seeking Behavior through the Re-Engineering of Vincamine’s Biological Activity

Abstract: Innovative discovery strategies are essential to address the ongoing opioid epidemic in the United States. Misuse of prescription and illegal opioids (e.g., morphine, heroin) has led to major problems with addiction and overdose. We used vincamine, an indole alkaloid, as a synthetic starting point for dramatic structural alterations of its complex, fused ring system to synthesize 80 diverse compounds with intricate molecular architectures. A select series of vincamine-derived compounds were screened for both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Aubé recently described a remarkable CtD protocol to access diverse steroid analogues . These strategies have employed gibberellic acid, adrenosterone, quinine, pleuromutilin, abietic acid, sinomenine, yohimbine, , and vincamine (Figure ) to generate skeletal and stereochemical diversity. Several interesting discoveries of first-in-class therapeutic leads and chemotypes that interrogate biological systems were reported using these approaches …”
Section: Introductionmentioning
confidence: 99%
“…Aubé recently described a remarkable CtD protocol to access diverse steroid analogues . These strategies have employed gibberellic acid, adrenosterone, quinine, pleuromutilin, abietic acid, sinomenine, yohimbine, , and vincamine (Figure ) to generate skeletal and stereochemical diversity. Several interesting discoveries of first-in-class therapeutic leads and chemotypes that interrogate biological systems were reported using these approaches …”
Section: Introductionmentioning
confidence: 99%
“…Vincamine ( 21 ) is a commercially available monoterpenoid indole alkaloid administered to patients to enhance global or regional blood flow [ 41 , 42 , 43 ]. In 2020, Huigens et al developed a remarkable Ctd strategy for vincamine ( 21 ), synthesizing eight stereochemically and structurally complex natural product-like scaffolds via the systematic application of a ring-distortion pathway including ring cleavage, ring rearrangement, and ring fusion reactions ( Scheme 2 ) [ 44 ]. First, two reported ring cleavage reactions were employed to afford two new natural product-like compounds, 22 and 23 .…”
Section: Complexity-to-diversity Strategy For Rapid Generation Of Ind...mentioning
confidence: 99%
“…Subsequently, a typical diversified synthetic method was applied to the newly synthesized eight natural product-like compounds, which produced an eighty-member small-molecule library with distinct natural product-like complex scaffolds. The robustness of this Ctd strategy for vincamine ( 21 ) has been successfully validated by the identification of a new bioactive compound, 33 , which has antagonistic activity against hypocretin type 2 receptor (HCRTR2) and hence possesses therapeutic potential against opioid abuse [ 44 ].…”
Section: Complexity-to-diversity Strategy For Rapid Generation Of Ind...mentioning
confidence: 99%
“…There are many instances of synthetic analogues enhancing the inherent therapeutic benefit of a natural product; however, we are interested in re-engineering the biological activity of select natural products to explore novel molecular scaffolds in multiple disease areas. To do this, our group has established a ring distortion platform using indole alkaloids as starting points in synthesis pathways aimed to dramatically alter their inherently complex, fused ring systems to generate diverse molecular architectures that could bind alternative disease-relevant targets. , …”
Section: Introductionmentioning
confidence: 99%
“…Tactically, ring distortion efforts prioritize synthetic sequences involving ring cleavage, ring expansion, ring fusion, and ring rearrangement reactions applied to available complex natural products. Our group has reported ring distortion efforts on yohimbine and vincamine, while others have successfully employed this approach on abietic acid, adrenosterone, gibberellic acid, lycorine, pleuromutilin, , quinine, sinomenine, and other steroidal systems . Re-engineered biological activities from ring distortion efforts include (1) ferroptocide, an anticancer agent produced from the antibiotic pleuromutulin, (2) V2a , a compound that inhibits morphine-seeking behaviors in mice from vincamine, and (3) Y7j , an antiplasmodial agent produced from yohimbine. In addition, we have shown that diverse compounds synthesized from vincamine and yohimbine display an array of unique antagonistic activity profiles against GPCRs of disease relevance, including cancer and addiction (168 GPCR panel at DiscoverX). , …”
Section: Introductionmentioning
confidence: 99%